(untitled) (DA NANG JOURNAL OF MEDICINE AND PHARMACY, 2026)
Objectives: This study aims to evaluate the value of Anti-Thyroglobulin (TgAb) levels after total thyroidectomy and examine the relationship between serum TgAb levels and thyroid cancer stages in patients with papillary thyroid carcinoma (PTC). Methods: Retrospective study of 160 papillary thyroid cancer patients after total thyroidectomy from 01/2023 to 07/2024 at Cho Ray Hospital. Results: The median TgAb level decreased significantly (p<0.05) from 3.26 IU/mL before radioiodine therapy to 1.50 IU/mL after treatment. Among patients with isolated PTC, TgAb concentrations were markedly lower (2.19 IU/mL) compared with those who had concomitant PTC and HT (42 IU/mL) with p<0.05. Before radioiodine therapy, 141 patients (88.13%) had TgAb levels within the normal range, and the number of patients with normalized TgAb levels increased to 144 (90%) after treatment, with no statistically significant difference (p>0.05). Conclusion: Among patients with isolated PTC, a proportion demonstrated elevated TgAb levels whereas the majority of patients with PTC accompanied by thyroiditis exhibited low TgAb concentrations